2010
DOI: 10.1097/mcp.0b013e3283323b73
|View full text |Cite
|
Sign up to set email alerts
|

Diet and asthma

Abstract: The available literature regarding dietary manipulation as asthma therapy is largely unconvincing. Although mechanistic and epidemiologic studies provide a rationale for diet therapies, there are few interventional studies with positive, clinically relevant endpoints. Future studies must include sufficient numbers of well selected patients and measure effects on exacerbations, symptoms, lung function, and medication use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 60 publications
0
10
0
1
Order By: Relevance
“…It has been suggested that dietary changes may contribute to this increase [9,10,11,12,13]. Flavonoids possess anti-inflammatory, antioxidant, anti-allergic, as well as immune-modulating effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that dietary changes may contribute to this increase [9,10,11,12,13]. Flavonoids possess anti-inflammatory, antioxidant, anti-allergic, as well as immune-modulating effects.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the interaction between genetic and environmental factors causes individuals to become sensitized to environmental allergens and to suffer from allergic diseases [5,6,7,8]. Since foods and beverages contain both allergy-promoting and anti-allergic nutrients, it has been proposed that dietary change may be one of the environmental factors responsible for such an increase [9,10,11,12,13]. Vitamins A, C, D and E, minerals, such as selenium, copper, zinc and magnesium, probiotics and omega-3 polyunsaturated fatty acids (PUFAs), as well as polyphenols have been shown to possess anti-allergic properties, whereas omega-6 PUFAs are precursors for leukotriene C4, which is known to promote allergic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Human intervention trials in established asthma have shown some benefit, but overall the results are mixed (2)(3)(4)(5)(6)(7). Although DHA and EPA can be interconverted, these two lipids also exert distinct effects, making the mechanistic interpretation of fish oil interventions difficult.…”
Section: Clinical Relevancementioning
confidence: 96%
“…Although the specific effect of kolaviron,[15] a biflavonoid constituent of G. kola on the airway, is not known with certainty, flavonoids possess antioxidant property that may underlie their effectiveness in asthma. [1617] Flavonoids also impair Ca 2+ release and utilization mechanisms in smooth muscles. [1819] In addition, flavonoids inhibit antigen-induced release of histamine from mast cells, basophils and also inhibit contractions induced by histamine, acetylcholine and phosphodiesterase.…”
Section: Discussionmentioning
confidence: 99%